2021
DOI: 10.2196/28309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Web-Based and In-Person Methods to Recruit Adults With Type 1 Diabetes for a Mobile Exercise Intervention: Prospective Observational Study

Abstract: Background Our clinical trial of a mobile exercise intervention for adults 18 to 65 years old with type 1 diabetes (T1D) occurred during COVID-19 social distancing restrictions, prompting us to test web-based recruitment methods previously underexplored for this demographic. Objective Our objectives for this study were to (1) evaluate the effectiveness and cost of using social media news feed advertisements, a clinic-based approach method, and web-based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 48 publications
4
15
0
Order By: Relevance
“…Adults with T1D were recruited to participate between November 2019 and August 2020 by a combination of social media advertising, snowball sampling, in-person, and other approaches previously described. 23 The inclusion criteria were aged 18 to 65 years with ≥6 months' diagnosis of T1D or other absolute insulin deficiency diabetes, inadequate baseline exercise patterns (<3 exercise sessions/wk), 2,24 English literacy, current user of a smartphone, and CGM. Exclusion criteria were chronic disease or physical disability requiring exercise adjustments outside the scope of the mobile intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults with T1D were recruited to participate between November 2019 and August 2020 by a combination of social media advertising, snowball sampling, in-person, and other approaches previously described. 23 The inclusion criteria were aged 18 to 65 years with ≥6 months' diagnosis of T1D or other absolute insulin deficiency diabetes, inadequate baseline exercise patterns (<3 exercise sessions/wk), 2,24 English literacy, current user of a smartphone, and CGM. Exclusion criteria were chronic disease or physical disability requiring exercise adjustments outside the scope of the mobile intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for our clinical assessments (Table 2) are detailed in our earlier manuscript. 23 Psychosocial instruments were also taken (see File , Supplemental Digital Content 1 , http://links.lww.com/JSM/A333).…”
Section: Methodsmentioning
confidence: 99%
“…Participant recruitment for in-person interviews through social media platforms, emails, and offline methods have had varying levels of success (Antoun et al, 2016; Ash et al, 2021; Gu et al, 2016; Nolte et al, 2015; Ramo & Prochaska, 2012). The most prevalent method appears to be Facebook, which is also well-documented within the medical research community as an effective recruitment method for sampling participants (Ash et al, 2021; Kapp et al, 2013; Pedersen & Kurz, 2016; Ramo & Prochaska, 2012; Smith et al, 2021; van Gelder et al, 2019). However, more research is needed to understand the effectiveness of Facebook outside of health studies.…”
Section: Optimizing Recruitment For Qualitative Researchmentioning
confidence: 99%
“…Previous studies have demonstrated the successful use of social media to improve study enrollment [2][3][4][5], particularly in recruiting children, a population traditionally challenging to reach [6][7][8]. In this study, we report the impact of using non-targeted, organic social media engagement to improve enrollment of children in a clinical research study of children with mild COVID-19 and assess the sociodemographic characteristics of enrollees.…”
Section: Introductionmentioning
confidence: 99%